Investment, financial markets and uncertainty - Arestis,Philip (2016)
Abstract This contribution provides a theoretical explanation of the accumulation process, which focuses on the presence of correlations between physical and financial investment, and how the latter could affect the former. It also accounts for the influence of the cost of external finance and the impact of financial uncertainty as proxied by the interest rate and the exchange rate respectively; thereby utilising the Keynesian notion of conventions in the determination of investment. Our model is estimated by applying the difference GMM and the system GMM to a panel of 14 OECD countries from 1970 to 2010.